Broadening bandgap of thermocrystal by tailoring air hole. (7th October 2020) - Xu, Kaiyuan; Jiang, Chun
Abstract: Thermocrystal is a new type of artificial periodic crystal structure, which reduces the thermal conductivity of materials. The main factor affecting the thermal conductivity of thermocrystals is the coverage area between the bandgap frequency range and the thermal spectrum. In this letter, we found that, compared with the circular air hole, the elliptical air hole can significantly improve the thermal bandgap of thermocrystal, which will effectively reduce the thermal conductivity. Among them, the cross-shaped ellipse air hole can widen the thermal bandgap of thermocrystal to more than twice. This improves the efficiency of heat transfer by 62%.